ISWI ATPase Smarca5 Regulates Differentiation of Thymocytes Undergoing β-selection. - Zikmund, Tomas (J Immunol, 2019)
Development of lymphoid progenitors requires coordinated regulation of gene expression, DNA replication and gene rearrangement. Chromatin remodeling activities directed by SWI/SNF2 superfamily complexes play important roles in these processes. Here we utilized a conditional knockout mouse model to investigate the role of Smarca5, a member of the ISWI subfamily of such complexes, in early lymphocyte development. Smarca5 deficiency results in a developmental block at the DN3 stage of αβ thymocytes and proB stage of early B cells at which the rearrangement of antigen receptor loci occurs. It also disturbs development of committed (CD73(+)) γδ thymocytes. The αβ thymocyte block is accompanied by massive apoptotic depletion of β-selected double negative DN3 cells and premitotic arrest of CD4/CD8 double positive cells. Although Smarca5-deficient αβ T cell precursors that survived apoptosis were able to undergo successful Tcrβ rearrangement, they exhibited a highly abnormal mRNA profile including persistent expression of CD44 and CD25 markers characteristic of immature cells. We also observed that the p53 pathway became activated in these cells and that a deficiency of p53 partially rescued the defect in thymus cellularity (in contrast to early B cells) of Smarca5-deficient mice. However, activation of p53 was not primarily responsible for the thymocyte developmental defects observed in the Smarca5 mutants. Our results indicate that Smarca5 plays a key role in the development of thymocytes undergoing β-selection, γδ thymocytes, and also B cell progenitors by regulating transcription of early differentiation programs.